Experimental response of an optical sensor used to determine the moment of blast by sensing the flash of the explosion - A. Roux; G.N. Nurick (South African Journal of Science, 2010)
The Council for Scientific and Industrial Research (CSIR) conducts research into the effect of underwater explosions on maritime structures and equipment. One of the parameters that are required to be measured to a large degree of accuracy is the shock wave velocity in close proximity (10 - 120 charge radii) of the explosion, without having to revert to the streak photography method. This distance is in the region where the near field crosses over to the far field, and it would be expected that the distance - time curve would not be linear. The streak photography method produces accuracy in the very near field of the explosion, but is not recommended for accurate measurements at distances beyond 20 charge radii. We investigated the response of an optical sensor constructed to measure the light flash of an underwater blast to determine the moment of explosion. By measurement of the time taken between this moment and the time when the shock wave reaches the pressure sensors, accurate measurements of the distance - time history (and hence shock wave velocity) could be calculated. Twelve general purpose phototransistors were used in a parallel configuration to enhance the sensitivity of the sensor. These transistors were connected directly to a conditioning amplifier which formed the interface between the transistors and the data acquisition equipment. The results that were obtained confirmed that the light intensity of the flash of the explosion increased to a maximum within several microseconds. Measurements of the average velocity of the shock wave propagation, based on the flash measurement as a marker, correlated to within 0.1%, meaning that this method of marking the moment of explosion to within several microseconds had been successful. This method can therefore be used in similar underwater blast measurement applications when a measurement marker of the moment of explosion is required.